ANALISIS RASIO KEUANGAN PELAKU USAHA SEKTOR INFORMAL - Benius Benius; Anta Lutfi Ana, Parista Kristina, Yanuar Budi Kurniawan, Jepri, Maria Vivi Arindha (CV. ADIBA AISHA AMIRA, 2024)
Financial management plays an important role in the development of Micro, Small and Medium Enterprises (MSMEs), especially in the informal sector such as the culinary industry in Indonesia. This study uses quantitative descriptive methods as the main tool in this study to evaluate the financial performance of informal sector traders in Palangka Raya City in 2024. from the ratio of profitability and also activity shows that financial management shows potential numbers. However, even so, the performance of the informal sector in Palangka Raya City in 2024 can be said to be efficient based on the results of the ratio analysis that has been carried out. Therefore, further improvement and development are needed to achieve the maximum potential of these informal sectors. This conclusion is expected to be a reference for business actors in managing and developing their business in the future